2014
DOI: 10.1016/j.rehab.2014.03.1262
|View full text |Cite
|
Sign up to set email alerts
|

Our experience with extracorporeal shockwave therapy (ESWT) in spastic children with cerebral palsy (CP)

Abstract: Introduction. ESWT refers to the use of Shock Waves in medical practice. It was used as an important tool in spasticity management of children with CP. The aim of our study was to evaluate the effect of a 3 session of ESWT on spastic upper and lower limbs muscles in children with CP. Methods. Sixty-three children (37 boys and 26 girls), mean age 99.57±53.74 months, were included in the study. We used focused ESWT, applied in 3 sessions during the admission of each child, on the mainly affected muscles, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Although their study included a control group, the small sample size, the shortterm follow-up (4 weeks), and the use of only subjective (MAS and ankle pRoM) or nonstandardized (baropodometry) measures of muscle stiffness represent important limitations compared to our research. In a 2014 study on a large group of 64 children with CP, Mirea et al (12) showed that ESWT (3 sessions, 500 SW per session, energy level 0.15 mJ/mm 2 , frequency 10 Hz) could decrease muscle spasticity at different anatomical sites. Although the sample size was large, the lack of a control group, the treatment of different muscles, the use of only subjective assessment tools (MAS, Gross Motor Function Classification System, Gross Motor Function Measure 66, and Questionnaire on Pain caused by spasticity), and the short-term follow-up are important weaknesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their study included a control group, the small sample size, the shortterm follow-up (4 weeks), and the use of only subjective (MAS and ankle pRoM) or nonstandardized (baropodometry) measures of muscle stiffness represent important limitations compared to our research. In a 2014 study on a large group of 64 children with CP, Mirea et al (12) showed that ESWT (3 sessions, 500 SW per session, energy level 0.15 mJ/mm 2 , frequency 10 Hz) could decrease muscle spasticity at different anatomical sites. Although the sample size was large, the lack of a control group, the treatment of different muscles, the use of only subjective assessment tools (MAS, Gross Motor Function Classification System, Gross Motor Function Measure 66, and Questionnaire on Pain caused by spasticity), and the short-term follow-up are important weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that upregulated neovascularization (6), neuroregeneration (7), enzymatic activities (8), anti-inflammatory effect (9), and recruitment of endogenous mesenchymal stromal cells (MSCs) (10) might be involved in the process. Over the last few years several studies have found ESWT to be effective for treating muscle contractures in children with CP via its neuromodulatory and rheological effects (11)(12)(13)(14)(15). However, until now only subjective or operator-dependent assessment tools have been used in order to measure the effects of ESWT on spastic muscles.…”
mentioning
confidence: 99%
“…The speculated mechanism of decreased spasticity immediate after a single ESWT may be related to changed muscle physical properties (thixotropy), such as breaking the functional links between actin and myosin. Titin-actin interaction can induce reduction in intrinsic stiffness of connective tissue in chronically hypertonic muscles as a result of being mechanically shaken (vibration) [ 25 26 ]. In addition, it has been hypothesized that the waves in ESWT can dilate blood vessels via enzymatic promotion [ 10 11 12 ] and non-enzymatic nitric oxide synthesis [ 13 ], thus subsequently inducing neovascularization, increasing the blood supply to the tissue, and modulating the secretion of interleukins and the activation of growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of ESWT in patients with cerebral palsy, it was reported that the effect lasted for up to four weeks when stimulation of 0.030mJ/mm² for 1500 times in the soleus muscle and medial and lateral gastrocnemius was performed to pediatric patients once a week [40]. In cerebral palsy patients with extremely stiff upper and lower muscles, the effect of treatment with 2000 times of stimulation in 0.10mJ/mm² for three times a week lasted for two months; however, the effect of treatment was returned to pre-treatment levels after three months, suggesting that additional extracorporeal shock waves may be necessary after three months of previous treatment [41].…”
Section: B Indications For Extracorporeal Shockwave Therapymentioning
confidence: 99%